TINGKAT STRES PETUGAS PEMANDU LALU LINTAS PENERBANGAN - Widodo, Erna S; Fahmi, Rizki; Pantaryanto, Novy (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2015)
Jakarta Air Traffic Service Centre unit Aerodrome Control Tower is a unit that is responsible for providing pilotage services cost in the region of Soekarno-Hatta International Airport, per day, serve at least 1000 flight. The research objective is to analyze and determine the level of stress at work in air traffic control officer. To solve the problems mentioned above, the authors use a mixed method approach is a method of quantitative and qualitative methods as a whole --- which assures that there is a significant relationship between work stresses in the work with the performance of air traffic control personnel unit Aerodrome Control Tower.